Epistemologi Akuntansi sebagai Konstruksi Sosial: Telaah atas Peran Nilai dan Budaya dalam Pembentukan Pengetahuan Akuntansi - Fitri Nurhayati M; Dita Aulia Buata; Sri Astuti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Accounting has long been perceived as a technical system that is objective and value-free; however, this view has increasingly been questioned by epistemological debates in accounting research. This study aims to examine accounting epistemology as a social construction shaped by values, culture, and social practices. A qualitative approach with a literature review method is employed to analyze conceptual arguments and empirical findings from prior studies. The results indicate a paradigm shift from positivistic accounting toward interpretive and critical approaches that recognize the importance of social and cultural contexts. The findings further reveal that values and culture do not merely influence accounting practices but also shape the production and legitimation of accounting knowledge. Accounting is therefore understood as a meaningful social practice rather than merely an economic recording tool. This study concludes that accounting epistemology is inherently contextual and embedded in the values of the society in which it develops. Consequently, the advancement of accounting knowledge requires the recognition of epistemological plurality to ensure greater relevance, reflexivity, and responsiveness to diverse social realities.This study aims to examine the epistemology of accounting as a social construction by exploring the role of values and culture in the formation of accounting knowledge. This research employs a literature review method by analyzing various scholarly works, books, and academic articles relevant to epistemology, social theory, and critical perspectives in accounting. The discussion focuses on how accounting knowledge is not purely neutral and objective, but is shaped through social interactions, interests, dominant values, and the cultural contexts in which accounting develops and is practiced.